Literature Review : PENGARUH RESISTANCE EXERCISE DENGAN MENGGUNAKAN ELASTIC BAND UNTUK EKSTREMITAS BAWAH TERHADAP KESEIMBANGAN PADA LANJUT USIA - Faika Nurkomala (2020)
Balance is the ability possessed by everyone in maintaining their position. Resistance training uses a rubber band that forms muscles that can enlarge muscles. Elderly in his life, physical, mental and social setbacks. This study was conducted to determine the effect of resistance training using a rubber band for the lower extremities on balance in the elderly. The method used in this study consisted of a literature review that collected several data sources, using electronic data sourced from Google Schoolar and Pubmed. The research sample uses 6 articles selected according to specified criteria. Assessment of the quality of research in this study uses the Scimago Journal & Country Rank (SJR). After analyzing the data, it was concluded that resistance training using rubber bands for lower extremities contributes to balance. Thus, resistance training using a rubber band for the lower extremities provides increased muscular strength to lower extremities which can increase balance efficiency to improve further.